Revision of the genus Odocnemis Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) from Turkey, the Caucasus and Iran with observations on feeding habits - Nabozhenko, Maxim; Keskin, Bekir (Zootaxa, 2016)
A revision of the genus Odocnemis of Turkey, the Caucasus and Iran is presented. Thirty species and four subspecies are distributed in this territory. The following 20 new species and subspecies are described: O. dichroa sp. n., O. allardi sp. n., O. merkli sp. n., O. seducta sp. n., O. aegaeica sp. n., O. euritopica sp. n., O. subtuberculigera sp. n., O. subtuberculigera thracica subsp. n., O. erseni sp. n., O. molecularica sp. n., O. shokhini sp. n., O. inornata sp. n., O. altimontana sp. n., O. amanosica sp. n., O. cordiformis sp. n., O. kakunini sp. n. O. evestigata sp. n., O. torosica sp. n., O. torosica subangulata subsp. n., Odocnemis hakkariensis sp. n. The name of the genus is feminine, therefore all species names are transformed from masculine to feminine. Almost all new taxa are described from Turkey; O. amanosica sp. n. is additionally recorded from Syria, O. allardi sp. n.—from Armenia, Azerbaijan (Nakhchivan) and Iran, O. kakunini sp. n. from Iran. New synonymies are established: Odocnemis anatolica (Pic, 1899) = Stenomax korbi Reitter 1902: 219, syn.n.; Odocnemis recticollis (Allard, 1877) = Stenomax kurdistanus Reitter, 1902: 221, syn.n.; Odocnemis punctata Allard, 1876 = Cylindronotus (Odocnemis) pseudoclarus Reitter, 1922, syn.n. The following lectotypes are designated: Helops (Odocnemis) anatolicus Pic, 1899, Helops (Stenomax) seriegranatus Seidlitz, 1896, Cylindronotus (Odocnemis) opertus Reitter, 1922, Stenomax recticollis Allard, 1876, Odocnemis punctata Allard, 1876, Helops (Odocnemis) protinus Reitter in Bodemeyer, 1900. Holotypes and paratypes of all other Turkish species of Odocnemis are studied. Two new combinations are established: Odocnemis gloriosa (Faldermann, 1837), comb. n. (from Nalassus Mulsant, 1854) and Odocnemis terminasianae (Nabozhenko, 2011), comb. n. (from Armenohelops Nabozhenko, 2002). Five species O. bosphoranus (Allard, 1876), O. amasiae (Seidlitz, 1896), O. scutellatus (Reitter, 1902), O. fundator (Reitter, 1908), O. strangulatus (Reitter, 1922)) are not revised in this work and will be included in the genus Armenohelops in a future revision. Three species which were previously recorded from Turkey erroneously (O. exarata (Germar, 1817), O. crenatostriata (Allard, 1877), O. caudata Allard, 1876) should be removed from the Turkish list. Eight species-groups are characterized in the paper. The following aspects are considered and discussed: classification of the genus, morphology and main evolutionary tendencies, distribution and bionomics. A key to the Turkish, Caucasian and Iranian species of Odocnemis is given.